2009
DOI: 10.1007/s10072-009-0159-y
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and outcome of thrombolytic therapy for acute stroke in Pakistan

Abstract: Our objective was to identify the outcome of patients treated with tissue plasminogen activator (r-tPa) in Pakistan and compare these data to available regional and international data. The charts of all patients treated with r-tPa for acute stroke at two centers in Pakistan (Aga Khan University, Karachi and Liaquat National hospital, Karachi) were retrospectively reviewed. We identified 21 patients. The utilization of tPa at Aga Khan Hospital was 18/1,185 patients (1.5%) from 2005 to 2007 while at Liaquat Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 12 publications
1
28
3
Order By: Relevance
“…A recent systematic review 17 assessed the global use of rtPA for AIS among 214 countries and found that only 54 (25%) of these countries reported its administration, ranging from as low as 3% (1 of 36) of low-income, to 13% (7 of 54) of lower middle-income, to 28% (15 of 54) of upper middle-income, and to 44% (31 of 70) of highincome countries. 17 In comparison, access to rtPA in Iran is lower than in most of the developed countries [18][19][20][21][22][23][24][25] but comparable with other developing countries [26][27][28][29][30][31][32] ( Fig 2). The barriers of timely administration of rtPA in developing countries include limited resources, prehospital delay, sparse numbers of stroke units, 16,33 poor stroke awareness in the general population, 33 lack of general knowledge and professional education, 33,34 the high cost of rtPA, lack of insurance coverage, low socioeconomic status of patients, 16,33 and physician reluctance and concerns about the benefits compared with its serious side effects, especially bleeding.…”
Section: Discussionmentioning
confidence: 86%
“…A recent systematic review 17 assessed the global use of rtPA for AIS among 214 countries and found that only 54 (25%) of these countries reported its administration, ranging from as low as 3% (1 of 36) of low-income, to 13% (7 of 54) of lower middle-income, to 28% (15 of 54) of upper middle-income, and to 44% (31 of 70) of highincome countries. 17 In comparison, access to rtPA in Iran is lower than in most of the developed countries [18][19][20][21][22][23][24][25] but comparable with other developing countries [26][27][28][29][30][31][32] ( Fig 2). The barriers of timely administration of rtPA in developing countries include limited resources, prehospital delay, sparse numbers of stroke units, 16,33 poor stroke awareness in the general population, 33 lack of general knowledge and professional education, 33,34 the high cost of rtPA, lack of insurance coverage, low socioeconomic status of patients, 16,33 and physician reluctance and concerns about the benefits compared with its serious side effects, especially bleeding.…”
Section: Discussionmentioning
confidence: 86%
“…Following its success, “Brazilian National Stroke Policy Act” was implemented, which reduced the cost of rTPA from USD 2,000/patient to USD 540/patient [27]. In Egypt, <1% of eligible patients were thrombolysed [45,] while no more than 2% of patients are thrombolysed in Pakistan and Iran [34,50]. This figure is somewhat better in the “Indo-US Collaborative Stroke Project,” where 227 of 2066 (11%) patients in 5 centres across the country received thrombolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Over 80% of all stroke deaths, worldwide, occur in the developing countries (7). Adults in low- and middle-income countries are at a 30% greater risk of death from non-communicable diseases than their counterparts in high-income countries (8), nonetheless, in developing countries thrombolytic therapy for patients with AIS is available for only 1–3% of patients and mostly in urban areas (9-13), while in developed countries, this ratio is as high as 10% (14) or even higher (15). Iran is a developing country with stroke prevalence of 23–103 per 100,000 population (7, 13).…”
Section: Introductionmentioning
confidence: 99%